2021
DOI: 10.1042/bsr20210362
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbial alterations in neonatal jaundice pre- and post-treatment

Abstract: Neonatal jaundice is a common disease that affects up to 60% of new-borns. Herein, we performed a comparative analysis of the gut microbiome in neonatal jaundice and non-neonatal jaundice infants and identified gut microbial alterations in neonatal jaundice pre- and post-treatment. We prospectively collected 232 faecal samples from 51 infants at 5 time points (0, 1, 3, 6 and 12 months). Finally, 114 samples from 6 neonatal jaundice infants (NJI) and 19 non-NJI completed MiSeq sequencing and analysis. We charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…These data indicate that the gut microbiota are important participants in the bilirubin metabolism. An increase in diversity and abundance is a common manifestation of gut microbiota disorders in NH (17,18). The present study found that 24 h of phototherapy markedly reduced the diversity and abundance of intestinal flora, suggesting that phototherapy may also partially reverse the microflora changes caused by NH.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…These data indicate that the gut microbiota are important participants in the bilirubin metabolism. An increase in diversity and abundance is a common manifestation of gut microbiota disorders in NH (17,18). The present study found that 24 h of phototherapy markedly reduced the diversity and abundance of intestinal flora, suggesting that phototherapy may also partially reverse the microflora changes caused by NH.…”
Section: Discussionsupporting
confidence: 58%
“…S. salivarius can release bacteriocins (salivary A5 and B) (23-25), thereby antagonizing opportunistic or pathogenic bacteria. As aforementioned, the diversity and abundance of the gut microbiota in newborns with hyperbilirubinemia are increased and contain a number of opportunistic pathogens (17,18). Therefore, the increase in the abundance of S. salivarius after phototherapy may partially improve intestinal defense function.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that if the colonization process starts in utero or during birth, interventions to influence the composition of the infant’s gut microbiota may need to be started early. The importance of an early intervention is emphasized by previous reports that the meconium microbiota has been found to be associated with the subsequent health of the infants, such as neonatal jaundice, 46 , 61 , 62 NEC, 40 , 60 , 63 , 64 allergies and atopy, 65 , 66 disrupted infant growth, 10 , 53 , 67 71 early-onset neonatal sepsis (EONS) 60 , 72 , 73 and other conditions. 9 , 60 , 74 76 One possible intervention to alter the gut microbiota may be the use of probiotics, which have been found to have a positive effect on the newborn gut.…”
Section: Discussionmentioning
confidence: 99%
“…After organizing the sequencing data and summarizing metadata from the mapping les (the mapping le from Bosman et al ( 16) was obtained through email), Vsearch v2.14.2 (18) and Usearch v11.0.667 (19) were applied for sequence preprocessing. Vsearch was rst used to merge the sequencing data with paired reads (15,16,20,21), and remove the barcodes, primers and redundancy, while non-cluster denoising was performed using Usearch. A high-quality ltered sequence with more than 97% consistency was clustered to obtain amplicon sequence variants (ASVs).…”
Section: Sequence Preprocessing and Taxonomic Pro Lingmentioning
confidence: 99%